2022
DOI: 10.3390/ijerph19042343
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts and Suicides as a Result of Poisoning and under the Influence of Xenobiotics in Poland in 1999–2020

Abstract: Background: The most common method of suicide in Poland is hanging, especially among men. However, women tend to overdose on medications to commit suicide. Considering suicide attempts, poisoning, which involves overdosing various substances, is the most commonly used method. The purpose of the present study was to analyze suicide attempts by intoxication, suicides, and substances that influenced the state of consciousness of suicide victims in Poland in the years covered by the study. Methods: A descriptive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, a national study in Iran confirmed our findings that drug poisoning was the most common attempt suicide, while hanging was the most common suicide method [ 14 ]. Poisoning was also identified as the most common suicide method by studies in other countries, such as Poland and India [ 43 , 44 ]. One of the most important reasons for the high prevalence of medication-related suicide attempts is the easy access of people to high-usage drugs such as acetaminophen, painkillers, antibiotics, and even benzodiazepines, and the lack of strictness of pharmacies in selling drugs without a doctor’s prescription in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a national study in Iran confirmed our findings that drug poisoning was the most common attempt suicide, while hanging was the most common suicide method [ 14 ]. Poisoning was also identified as the most common suicide method by studies in other countries, such as Poland and India [ 43 , 44 ]. One of the most important reasons for the high prevalence of medication-related suicide attempts is the easy access of people to high-usage drugs such as acetaminophen, painkillers, antibiotics, and even benzodiazepines, and the lack of strictness of pharmacies in selling drugs without a doctor’s prescription in Iran.…”
Section: Discussionmentioning
confidence: 99%